2022
DOI: 10.3390/ijms23126526
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and Venous Leg Ulcer Healing—A Systematic Review

Abstract: Venous leg ulcers (VLUs) are the most common type of leg ulcers with a significant socioeconomic burden due to slow healing. Cytokines may be involved in the pathogenesis of VLUs. In this systematic review, our objective was to investigate the association between cytokine levels, including growth factors, with the healing of VLUs. PubMed, Embase, Web of Science and Cochrane Library were searched from their inception to August 2021. We retrieved 28 articles investigating 38 different cytokines in 790 patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 99 publications
0
10
0
Order By: Relevance
“…Harris et al 63 VLUs. 64 In contrast, an analysis by Burian et al 65 found no significant differences in the levels of the cytokines studied and determined that the relationship between cytokine levels and ulcer healing is consequential or coincidental.…”
Section: Resultsmentioning
confidence: 97%
“…Harris et al 63 VLUs. 64 In contrast, an analysis by Burian et al 65 found no significant differences in the levels of the cytokines studied and determined that the relationship between cytokine levels and ulcer healing is consequential or coincidental.…”
Section: Resultsmentioning
confidence: 97%
“…Angiogenesis and growth factor production is essential for diabetic wound healing. PDGF is currently the only growth factor treatment for diabetic wounds approved by FDA ( 7 ). FGF2 has been reported to contribute critically to the modulation of scar formation ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of inflammatory mediators and the infiltration of immune cells, including neutrophils, macrophages, and lymphocytes, into the venous wall are instrumental in the remodelling processes, endothelial dysfunction, and tissue damage, thereby amplifying ulceration risks. [17][18][19][20] Notwithstanding the established association between inflammation and varicose veins, the specific linkage between inflammatory markers and the onset of venous wounds remains ambiguous. Mendelian randomization (MR) has emerged as a potent analytical method, leveraging genetic variants as instrumental variables to deduce causal relationships between risk factors and disease manifestations, circumventing confounding factors and reverse causation.…”
Section: Introductionmentioning
confidence: 99%